Securitization and Desecuritization of Migration in Indonesia - Nurul Azizah Zayzda; Maiza Hazrina Ash-Shafikh; Ayusia Sabhita Kusuma (Jember University Press, 2019)
This paper seeks to explain through an analysis using securitization theory, the dynamics of securitization and desecuritization of migration in Indonesia with a particular emphasize on the forced migration issues in the Southeast Asian region. This paper provides an analysis on the speech act represented in the legal documents or policy papers and the non-discursive practices demonstrated by the authorities in the security-related migration regulation and refugees protection. Both the occurrence of securitization and desecuritization is elaborated. The securitization is understood to take place when policy or legal documents as well current practices construct assumptions that migrants, including irregular or forced migrants pose certain threats to society. The desecuritization, meanwhile, is found in legal documents and practices that weaken the security claims regarding the migrants. It is argued here that desecuritization takes place in the midst of securitization and shifts the language of security of forced migration in regional level. The extent to which the perception of security threats imposed by the migratory process has been shifted can be reviewed in the policy changes by other individual states in the region and the international institutions working within regarding to refugees protection.